Versão breve da social rhythm metric: um instrumento para avaliar ritmo social de pacientes com acidente vascular cerebral - Fonsêca, Ricardo Diego Rimenez Gurgel da (2012)
Stroke is a neurological disorder caused by restriction of blood flow to the brain, which generates directly a deficit of functionality that affects the quality of life of patients. The aim of this study was to establish a short version of the Social Rhythm Scale (SRM), to assess the social rhythm of stroke patients. The sample consisted of 84 patients, of both sexes, with injury time exceeding 6 months. For seven days, patients recorded the time held 17 activities of SRM. Data analysis was performed using a principal components factor analysis with varimax rotation of the full version of SRM in order to determine which activities could compose brief versions of SRM. We then carried out a comparison of hits, the ALI (Level Activity Index) and SRM, between versions, by Kruskal-Walls and the Mann-Whitney test. The Spearman correlation test was used to evaluate the correlation between the score of the full version of SRM with short versions. It was found that the activities of SRM were distributed in three versions: the first and second with 6 activities and third with 3 activities. Regarding hits, it was found that they ranged from 4.9 to 5.8 on the first version; 2.3 to 3.8 in version 2 and 2.8 to 6.2 in version 3, the first the only version that did not show low values. The analysis of ALI, in version 1, the median was 29, in version 2 was 14 and in version 3 was 18. Significant difference in the values of ALI between versions 1 and 2, between 2 and 3 and between versions 1 and 3. The highest median was found in the first version, formed by activities: out of bed, first contact, drink coffee, watch TV in the evening and go to bed. The lowest median was observed in the second version and this was not what had fewer activities, but which had social activities. The medians of the SRM version 1 was 6, version 2 was 4 and version 3 was 6. Significant difference in the values of SRM between versions 1 and 2 and between 2 and 3, but no significant difference between versions 1 and 3. Through analysis, we found a significant correlation only between the full version and the version 1 (R2 = 0.61) (p <0.05), no correlation was found with version 2 (R2 = 0.007) nor with version 3 (R2 = 0.002), this was finally a factor to consider version 1 as the short brazilian version of the Social Rhythm Metric for stroke patients